Pemanfaatan Limbah Nanas (Ananas Comosus L. Merr) Sebagai Penggumpal Alami Pada Proses Pembuatan Tahu Kedelai - Elfiana Elfiana; Salmyah Salmyah; Rauzatul Aulia (Politeknik Negeri Lhokseumawe, 2025)
Pineapples contain many useful ingredients, one of which is acid and the enzyme bromelain. This content is also found in pineapple waste which we can use as an alternative coagulating agent for tofu. This content is able to bind proteins into lumps in soybean juice to form curd (clumps of tofu). In this research we used pineapple waste to extract the acid content remaining in pineapple waste. This is also an effort and solution to reduce waste in the surrounding environment and add economic value to pineapple waste which is usually not utilized. This research aims to find out how the volume of pineapple waste juice and soaking time influence the tofu making process. The process method is that the soybeans are soaked for 6 soaking times each; 8; 10; and 12 hours. After soaking the soybeans, they are ground using a grinder, then the soybean juice is filtered from the dregs and boiled for about 15 minutes, then the coagulation process is carried out with variations in the volume of pineapple waste juice, namely 20; 40; 60; 80 and 100 ml. Put the soybean juice that has coagulated into the mold, wait until the tofu forms. The results of the research showed that the best water content, texture and protein content were obtained from making tofu by soaking for 6 hours with 60 ml of pineapple waste coagulating agent. The water content result was 60%, which was liked by many panelists, the texture test was 212.5 gf and the protein value was 15.63%. The results obtained in this research are in accordance with SNI 01-3142-1998.